1987
DOI: 10.1139/b87-043
|View full text |Cite
|
Sign up to set email alerts
|

Leakage of sodium ions from plasma membrane modification, associated with permeability change, in host cells treated with a host-specific toxin from a Japanese pear pathotype of Alternaria alternata

Abstract: 1987. Leakage of sodium ions from plasma membrane modification, associated with permeability change, in host cells treated with a host-specific toxin from a Japanese pear pathotype of Alternaria alternata. Can. J. Bot. 65: 330-339. Ultrastructural sites for leakage of sodium ions in susceptible leaves of Japanese pear treated with AK-toxin I were examined by a precipitation method for sodium ions and analytical electron microscopy. The earliest effect of the toxin (50 pgImL) appeared on the plasmodesmatal regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…The severely damaged subtype of plasma membrane modification is typical in susceptible genotypes of Japanese pear plants treated with the toxin. The toxin caused permeability changes in host cells but not in fungal cells within 2 min of toxin exposure (Park et al 1976) and caused changes in the plasma membrane within 5 min of exposure (Park et al 1987b). The permeability dysfunction was probably associated with the modifications because the modifications were observed specifically at plasma membranes near the plasmodesmata of the toxin-treated host cells ( Fig.…”
Section: Mode Of Action Of Alternaria and Stemphylium Host-specific Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The severely damaged subtype of plasma membrane modification is typical in susceptible genotypes of Japanese pear plants treated with the toxin. The toxin caused permeability changes in host cells but not in fungal cells within 2 min of toxin exposure (Park et al 1976) and caused changes in the plasma membrane within 5 min of exposure (Park et al 1987b). The permeability dysfunction was probably associated with the modifications because the modifications were observed specifically at plasma membranes near the plasmodesmata of the toxin-treated host cells ( Fig.…”
Section: Mode Of Action Of Alternaria and Stemphylium Host-specific Tmentioning
confidence: 99%
“…Any data concerning any association were only circumstantial. To further examine any possible association, a cytochemical method using pyroantimonate fixation was used in a subsequent experiment (Park et al 1987b). Some cellular ions of plant cells can be visualized using pyroantimonate fixation with EM.…”
Section: Sites Of Ion Leakagementioning
confidence: 99%
“…It was observed in an ultrastructural study of AK-toxin I-treated Japanese pear leaves that a large number of exocytotic Golgi vesicles appeared to specifically fuse on invaginated plasma membranes of the susceptible pear cells, suggesting that the formation of plasmalemmal invaginations was associated with the exocytotic Golgi vesicles15). Additionally, Park et al 14) described in the study of the modifications caused by AK-toxin I that the ions in the susceptible cells were leached from the plasma membranes in the vicinity of plasmodesmata by the toxin treatment. They concluded that the ion-leakage was associated with the plasma membrane modifications.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed it by using precipitation method and analytical electron microscopy and reported deposition of magnesium ions immediately after exposure to toxin. The deposition ofMg and Na ions was reported for AK -toxin and AF -toxin (Park et al, 1987).…”
Section: Mode Of Action Of Phytotoxinsmentioning
confidence: 92%